Influence of biogas mixing parameters on the combustion and emission characteristics of diesel RCCI engine - Said, M.A. (Elsevier B.V., 2021)
Reactivity-controlled compression ignition (RCCI) combustion involves in-cylinder fuels blending of varying reaction rates to enhance the combustion magnitude by stratification. Nitrogen oxides (NOx) and soot control techniques increase carbon monoxide (CO) and unburned-hydrocarbon (UHC) emissions in RCCI at low loads. A modified injection and proper Biogas mixing may reduce further CO, UHC, and trade-off with other emissions. The effects of loads (5.5 and 6.5 bar IMEP), port mixing distances (0â100), swirl ratios (0â80), and biogas pressures (1â4 bar) on the mixture distribution and emissions were evaluated experimentally, at 1600 rpm. Exergy analysis and combustion kinetics were applied for more understanding of emissions attributes. The process at 5.5 bar IMEP improves mixture homogeneity, uniform fuel stratification and reduces emissions across the mixing intervals. Injection at valve reduces CO, UHC, and NOx emissions by 11.54, 9.38, and 33.75 at 5.5 bar IMEP. Operating at the valve, 80 swirl ratio and 1 bar pressure further reduce the UHC (115.77 ppm), NOx (3.89 ppm), and PM (5.29 ppm) emissions by 1.94, 49.94, and 77.42, than normal airflow. Thus, injecting biogas of low pressure at the valve amidst a stream of swirling air contributes to trade-off reduction techniques at low load. Â© 2021 THE AUTHORS